2013
DOI: 10.3126/jonmc.v2i1.7675
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter Species: Phenotypic Characterization And Antimicrobial Resistance

Abstract: Background: Acinetobacter species is ubiquitous, aerobic gram-negative coccobacilli that are now emerging as an important nosocomial pathogen. Objectives: The present study was designed to know the prevalence of Acinetobacter in various clinical samples, their characterization and their antibiotic susceptibility pattern in B.P. Koirala Institute of Health and Sciences, Dharan. Methodology: Hundred Acinetobacter isolates obtained from different clinical specimens were taken. Identification to species level was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
6
12
0
Order By: Relevance
“…In our study, the resistance rate against tested beta-lactam antibiotics ranged from 76% to 89% throughout the hospital, from 87 to 98% in the ICUs and 59-75% in the other units. This rate is comparable to that observed in Asia, where it ranged from 56 to 94% [ 14 , 20 , 27 , 32 ]. In a Libyan study, the resistance was of 62.3 to 98.8% throughout the studied hospital, 71.6-100% in the ICUs and from 42.6 to 96.2% in the other units [ 31 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, the resistance rate against tested beta-lactam antibiotics ranged from 76% to 89% throughout the hospital, from 87 to 98% in the ICUs and 59-75% in the other units. This rate is comparable to that observed in Asia, where it ranged from 56 to 94% [ 14 , 20 , 27 , 32 ]. In a Libyan study, the resistance was of 62.3 to 98.8% throughout the studied hospital, 71.6-100% in the ICUs and from 42.6 to 96.2% in the other units [ 31 ].…”
Section: Discussionsupporting
confidence: 83%
“…This rate is higher than that obtained in the United States and South Africa in a similar study where the resistance to ceftazidime was 52.1% and 68.4% respectively [ 8 , 21 ]. It ranges from 60 to 92.1% in studies in Asia [ 14 , 20 , 27 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…2) and Acb complex ( Table 5 Association between antibiotic resistance, ESBL production, MBL production, biofilm production and and piperacillin (80%) [25]. We found that the isolates resistance to amikacin were 44.7% and to ciprofloxacin 50.0% which was consistent with report by Shrestha et al [23]. [20].…”
Section: Biofilm Formationsupporting
confidence: 88%
“…baumannii) complex was predominating species (51.5%) in this study which was comparable to finding by Gupta et al 2015 from India which 9%) which was consistent with previously reported (25%) by Shrestha et al 2013[23].Resistance to cefepime (74.4%) and cefotaxime (73.8%) was detected in 74.4% and 73.8% of isolates respectively, followed by ceftazidime (72.5%), ceftriaxone (65%) and piperacillin 65%. Except piperacillin, antibiotic resistance patterns were comparable with that reported byShrestha et al 2013 in Nepal as ceftazidime (84%), ceftriaxone (66%), and piperacillin (96%)[23]. In addition, Amatya et al 2015 documented resistance towards ceftazidime (81%), cefotaxime (67.3%) and ceftriaxone (69.3%)[24].…”
supporting
confidence: 92%
“…Acinetobacter infections have been reported for almost all organ systems. It is usually an opportunistic pathogen as evidenced by the fact that 14% to 16% of infections are mixed infection [4]. Acinetobacter species is now recognized to be the species of great clinical importance being capable of causing life threatening infection including pneumonia, septicemia, wound sepsis, urinary tract infection, endocarditis and meningitis.…”
Section: Introductionmentioning
confidence: 99%